Possible futures for the Mediterranean: A cross-cutting approach of foresight analysis studies - SANNA Serena; LE TELLIER Julien (Scientific Annals of the Danube Delta Institute, 2013)
Which are the possible scenarios that await the Mediterranean by 2025? This question characterizes the Plan Bleu synthesis report developed in the framework of the Pegaso project – funded by the 7 thFramework Programme of the European Union and devoted to Integrated Coastal Zone Management in the Mediterranean and Black Sea. As one of the Regional Activity Centres of the United Nations Environment Programme’s Mediterranean Action Plan (UNEP/MAP) and as an observatory of the environment and development in the Mediterranean, Plan Bleu carried out various prospective studies to identify the threats and opportunities that arise in relation to sustainable development in the region, and the possible policy responses that might be needed. Plan Bleu developed recently a transversal analysis, synthetizing several relevant prospective studies at the Mediterranean level. Starting from the “business as usual” and alternative scenarios offered by those studies, this synthesis develops a cross-cutting approach between different dimensions of change (demographic trends, climate change, globalization) and topics (water, energy, coastal development, urbanization, tourism, maritime transportation). It also takes into account recent events and changes (i.e. global economic crisis, Arab Spring, institutional reforms) whose impacts on the future political trends could not be ignored. On the one hand the synthesis gathers a critical collection of scenarios for the Mediterranean, as outlined by a range of recent prospective studies. On the other hand, taking into account seeds of change and inflections of current trends, the reflection raises the crucial perspective towards a new regional prospective study at the 2050 horizon.